Impact of Zn2+ on ABC transporter function in intact isolated rat brain microvessels, human brain capillary endothelial cells, and in rat in vivo - Zaremba, Alexander; Helm, Frieder; Fricker, Gert (Molecular pharmaceutics, 2019)
ABC transporters act as efflux pumps, thereby influencing the pharmacokinetics and efficacy of many drugs. Zinc (Zn) is an essential trace element contributing to cellular growth and differentiation. It is increasingly recognized as an intracellular messenger. The present study aims at investigating the impact of Zn2+ on the function and regulation of ABC transporters at the blood-brain barrier (BBB). ABC transporter function was first studied in isolated rat brain capillaries. Zn2+ rapidly stimulated the activity of the multidrug resistance-related protein 2 (Mrp2), p-glycoprotein (P-gp), and breast cancer resistance protein (Bcrp). These short-term effects were independent of transporter de novo synthesis but based on Zn2+ triggering intracellular signaling to stimulate basal transport activity. Studies focused on Mrp2 and P-gp showed that Zn2+ induced signaling through an endothelin receptor type B (ETB)/nitric oxide synthase (NOS)/protein kinase C (PKC) pathway and caused, specifically, an activation of the isoform PKCα. Studies revealed signaling through the phosphatidylinositol 3-kinase (PI3K)/mechanistic target of rapamycin (mTOR) pathway, as well as induction of the downstream target serum- and glucocorticoid-inducible kinase 1 (SGK1). Short-term effects of Zn2+ were also demonstrated in human hCMEC/D3 cells. An initial in vivo study in rats suggested enhanced P-gp transport activity at the BBB due to elevated Zn2+ plasma levels. This work provides the first evidence for Zn2+ being a regulator of basal ABC transporter activity at the BBB, driving a rapid and nongenomic stimulation of transport function.